2005
DOI: 10.1242/jeb.01774
|View full text |Cite
|
Sign up to set email alerts
|

Female receptivity in butterflies and moths

Abstract: SUMMARY Female receptivity in butterflies and moths is influenced by a multitude of factors that vary between virgin and mated females, and is often affected by the quality and persistence of courting males. Mated females of polyandrous species frequently display a period of non-receptivity following mating, often resulting from factors transferred by the male at mating. Some of these compounds have a transient effect (e.g. anti-aphrodisiacs and mating plugs),whereas others induce long-term supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
98
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(99 citation statements)
references
References 107 publications
0
98
0
1
Order By: Relevance
“…stretch reception in the bursa copulatrix (Sugawara 1979)], the number of sperm stored by females at mating (e.g. Cook and Gage 1995;Cook and Wedell 1999), or possibly the amount of seminal fluids received by females (reviewed in Wedell 2005). Similarly, a few studies of crickets and bushcrickets (Orthoptera, Ensifera) have experimentally demonstrated that the duration of nuptial feeding, and hence gift size, influences female remating interval (Wedell and Arak 1989;Simmons and Gwynne 1991;Johnson et al 1999;Sakaluk et al 2006), whereas some studies found no effect of nuptial feeding on female remating behaviour (Brown 1997;Fleischman and Sakaluk 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…stretch reception in the bursa copulatrix (Sugawara 1979)], the number of sperm stored by females at mating (e.g. Cook and Gage 1995;Cook and Wedell 1999), or possibly the amount of seminal fluids received by females (reviewed in Wedell 2005). Similarly, a few studies of crickets and bushcrickets (Orthoptera, Ensifera) have experimentally demonstrated that the duration of nuptial feeding, and hence gift size, influences female remating interval (Wedell and Arak 1989;Simmons and Gwynne 1991;Johnson et al 1999;Sakaluk et al 2006), whereas some studies found no effect of nuptial feeding on female remating behaviour (Brown 1997;Fleischman and Sakaluk 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Malederived substances which affect female receptivity are common in insects (see e.g. Chapman et al 1998;Wedell 2005 for examples in Diptera and Lepidoptera). Thus, there is the possibility that, disguised in nuptial gifts, males may transfer substances, which regulate female remating behaviour (see also Leopold 1976;Chen 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Future development of genomic and post-genomic techniques will hopefully allow detailed examination of gene function to be expanded to nonmodel species such as moths. This may shed some light on why seminal factors have been found to be both very rapidly evolving and yet conserved across very distantly related groups (Wedell 2005). Simply finding rapid evolution is not evidence for sexual conflict, future studies need to demonstrate a relationship between costs to females and the rate of evolution of potentially manipulative substances such as Acps.…”
Section: Sexual Conflict: the State Of The Fieldmentioning
confidence: 99%
“…Such physiological changes are attributable not only to physical stimuli, such as penis insertion and stretch reception in the bursa copulatrix, but also other factors. During copulation, males transfer not only sperm, but also seminal fluid, spermatophores (including sperm cells), and mating plugs to females through genitalia (Chen, 1984;Eberhard, 1996;Simmons, 2001;Wedell, 2005). It is well-known for several insects that male-derived substances reduce female mating receptivity (e.g., Chen et al, 1988;Himuro & Fujisaki, 2008;Yamane et al, 2008).…”
Section: Introductionmentioning
confidence: 99%